Rondo in G major, op. 51, no. 2 - Beethoven, Ludwig van, 1770-1827:::Creator:::::::::::: (Vienna; Austria; Artaria)
Titelauflage of first edition of the Rondo in G major for piano, op. 51, no. 2, with plate no. 884; lacks price on t.p